Evaluasi Kualitas Pelayanan RSUD Kota Dumai Terhadap Pengguna Kartu BPJS Kesehatan Menggunakan Indeks Kepuasan Masyarakat - Hilda Wati; Dia Meirina Suri; Dedy Afrizal; Dila Erlianti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
PAN and RB Ministerial Regulations Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey, it is explained that every public service provider is obliged to evaluate the community satisfaction survey. This study aims to determine the Community Satisfaction Index of BPJS Health card users on Dumai City Hospital services. The method used is quantitative research with a descriptive approach. The research population is the community of BPJS Health card users who come to the Dumai City Hospital to get services. The results showed that the Community Satisfaction Index of BPJS Health card users for Dumai City Hospital services got an IKM value of 74.73. Based on the IKM value, the service performance of the Dumai City Hospital is categorized as Good with Service Quality being "B".